Trends and constraints of utilization of preserved cowpea leaves among households in arid and semi-arid lands in Kenya: a convergent mixed method study - J. O. Owade; G. O. Abong’; M. W. Okoth; A. W. Mwang’ombe (CABI Agriculture and Bioscience)
Abstract Background As much as local communities have employed traditional techniques of preservation to enhance availability and utilization of cowpea leaves, the efficiency of these techniques in achieving food security need to be established. The current study sought to document trends and constraints of utilization of preserved cowpea leaves in the arid and semi-arid lands (ASALs) in order to overcome of seasonal availability of the vegetable. Method A mixed method convergent design that included household survey of randomly sampled cowpea producing households and focus group discussion and key informant interviews with stakeholders in the ASAL areas of Kitui and Taita Taveta Counties of Kenya was conducted. Results The study found that the utilization of preserved forms of cowpea leaves in the in-season was by 58% of the respondents. Three quarters (73.6%) of the households could not get the vegetables from their own sources during scarcity, whereas 25% did not consume the vegetables at all at such times. The preserved forms of the vegetables was utilized among 24.0% of the households, with significantly (p < 0.05) higher utilization in less arid areas. Households that were involved in commercialization of cowpea leaves and sale of the preserved forms in the open air market had significantly higher likelihood (p < 0.001, OR = 2.47 and p < 0.001, OR = 2.3, respectively) of utilization of the vegetables during scarcity. Emerging themes from the qualitative survey showed that weaknesses in the policy environment, stakeholder interest, marketing and accessibility to proper equipment were the deterrents of traditional preservation of the vegetable. Conclusion In conclusion, the preserved forms of cowpea leaves promoted availability of the vegetable especially in the dry seasons. In as much as there is limited practising of preservation of the vegetables, its availability is enhanced through dehydration and other value-addition techniques among a significant number of the households.